2021
DOI: 10.1186/s41824-021-00098-y
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of SPECT/CT arthrography in patients with suspected aseptic joint prostheses loosening

Abstract: Purpose To evaluate the diagnostic accuracy of SPECT/CT arthrography in patients with suspected aseptic prosthesis loosening following hip and knee arthroplasty. Methods A retrospective review of 63 SPECT/CT arthrogram studies (36 knees and 27 hips) between February 1, 2013, and July 1, 2018, was conducted. All patients underwent clinical and radiologic evaluation as part of their assessment for persistent pain following hip and knee arthroplasty. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Better diagnostic performance for tibial component. A negative result excluded with high accuracy a pathological condition Bao et al [ 42 ] 36 Diagnostic retrospective III TKA 99m Tc Sulf Colloid i.a Intraoperative, follow-up 0.50 0.97 SPECT/CT arthrography showed high accuracy for detecting loosening in painful knee arthroplasty and excluding pathological condition. They showed that a detection of tracer activity along the bone interface was related to aseptic loosening Chew et al [ 43 ] 44 Diagnostic retrospective III TKA 99m Tc Ca Phyt i.a Intraoperative 0.75–0.86 0.63–0.86 They reported different diagnostic performance values according to the anatomical place of the knee replacement.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Better diagnostic performance for tibial component. A negative result excluded with high accuracy a pathological condition Bao et al [ 42 ] 36 Diagnostic retrospective III TKA 99m Tc Sulf Colloid i.a Intraoperative, follow-up 0.50 0.97 SPECT/CT arthrography showed high accuracy for detecting loosening in painful knee arthroplasty and excluding pathological condition. They showed that a detection of tracer activity along the bone interface was related to aseptic loosening Chew et al [ 43 ] 44 Diagnostic retrospective III TKA 99m Tc Ca Phyt i.a Intraoperative 0.75–0.86 0.63–0.86 They reported different diagnostic performance values according to the anatomical place of the knee replacement.…”
Section: Resultsmentioning
confidence: 99%
“…Bo Bao [ 42 ] reported on a retrospective cohort of 36 patients who underwent clinical and radiological evaluation for persistent pain following knee arthroplasty. With a medium risk of bias under the QUADAS-2 tool (explained by the flow and timing domain, as intraoperative findings and/or clinical or radiological evaluations were used as the reference standard), the authors reported a SEN of 0.50 [95% CI: 0.01–0.99] and a SPE of 0.97 [95% CI: 0.85–1.00] for the SPECT/CT arthrogram in detecting aseptic loosening.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, aseptic loosening is often only confirmed intra- or postoperatively, with the preoperative assessment frequently being a misdiagnosis of a low-grade infection [ 27 ]. Several radionuclide imaging techniques—scintigraphic [ 28 , 29 ] and tomographic [ 30 , 31 , 32 ]—have been implemented to provide more conclusive diagnoses of aseptic loosening [ 24 ]; radionuclide imaging has also been used to detect periprosthetic joint infection with reasonable success, but these advanced imaging techniques are time-consuming and only available at specialist centres.…”
Section: Introductionmentioning
confidence: 99%